Does integrated medical insurance system alleviate the difficulty of using cross-region health Care for the Migrant Parents in China-- evidence from the China migrants dynamic survey - Chao Ma; Shutong Huo; Hao Chen (BMC, 2021)
Abstract Background Many internal migrants during the urbanization process in China are Migrant Parents, the aging group who move to urban areas to support their family involuntarily. They are more vulnerable economically and physically than the younger migrants. However, the fragmentation of rural and urban health insurance schemes divided by "hukou" household registration system limit migrant's access to healthcare services in their resident location. Some counties have started to consolidate the Urban Resident Basic Medical Insurance (URBMI) and the New Rural Cooperative Medical Scheme (NRCMS) as one Integrated Medical Insurance Schemes (IMIS) from 2008. The consolidation aimed to reduce the disparity between different schemes and increase the health care utilization of migrants. Results Using the inpatient sample of migrant parents from China Migrants Dynamic Survey in 2015, we used Ordinary Least Squares (OLS) for regression models. We found that the migrant parents covered by the IMIS are more likely to choose inpatient services and seek medical treatment in the migrant destination. We further subdivide Non-IMISs into NCMSs and URBMIs in the regression to alleviate the doubt about endogenous. The results revealed that the migrant parents in IMIS use more local medical services than both of them in URBMI and NCMS. Conclusions The potential mechanisms of our results could be that IMIS alleviates the difficulty of seeking medical care in migrant destinations by improving the convenience of medical expense reimbursement and enhancing health insurance benefits.